Effect of blue laser on viability of Proteus mirabilis - Funjan, Mawada M. (Iraqi Journal of Science, 2021)
The usage of blue laser has been considered as a therapeutic approach to prohibit the viability of bacterial species, but there is no agreement about optimum parameters to be used. The aim of this project is to study the influence of blue laser (450 nm) on the viability of the gram-negative bacteria Proteus mirabilis isolated from burn wounds, using different exposure times (i.e. doses) in vitro. Seventy swab samples were collected from burn wounds of patients admitted to the burns unit in AL-Yarmouk teaching hospital in Baghdad, during the period from June to August 2019. The Bacteria were isolated and identified depending on their culture characteristics, biochemical tests, gram staining, and morphology, being finally confirmed by API 20E Test System. By using the disk diffusion method, susceptibility of the isolates to 12 different antibiotics was examined. One isolate of P. mirabilis was elected according to susceptibility to all antibiotics used. To prepare bacterial solution, P. mirabilis was mixed with normal saline solution. Dilution of 10-6 cell/ml for p. mirabilis was selected from other serial dilutions. A number of colonies and colony forming units (CFUs/ml) were achieved and correlated to controls. P. mirabilis was irradiated by blue diode laser (450 nm, 500mw) and exposed to different doses (24, 48, 72, 96, 120J/cm2) corresponding to respective exposure times (4, 8,12,16,20 minutes). The results of antibiotic susceptibility test indicate that the entire isolates of P. mirabilis were multidrug resistant. With the increase in laser dose (exposure times), the number of colonies and CFUs/ml were reduced, reaching a highest inhibition in CFU/ml at exposure time of 20 minutes, i.e. a dose of 120J/cm2 , with irradiance of 0.1 watt/ cm2. No significant reduction was recorded in CFU/ml at exposure time of 4 min (a dose of 24J/cm2). As a conclusion, the blue laser irradiation at wavelength of 450 nm and 500mw had antibacterial effects on P. mirabilis isolated from burn wounds with irradiance of 0.1watt/cm2 in vitro, as evidenced by the effective reduction in the viability of bacteria at a dose of 120J/cm2 corresponding to exposure time of 20 minutes.